2018
DOI: 10.1111/jopr.12771
|View full text |Cite
|
Sign up to set email alerts
|

Translucency of Zirconia Ceramics before and after Artificial Aging

Abstract: Aging reduced the translucency in all specimens tested. Furthermore, translucency differed between the zirconia brands tested. Nevertheless, the differences were below the detectability threshold of the human eye. The aging process can influence the translucency and thus the esthetic outcome of zirconia restorations; however, the changes in translucency were minimal and probably undetectable by the human eye.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
2

Year Published

2019
2019
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 50 publications
0
30
2
Order By: Relevance
“…On the other hand, these finding are in contradiction with the results reached by another study (22) in which accelerated aging had an effect on color and translucency of different zirconia brands. The difference in results may be attributed to the different methodology of both studies.…”
Section: Dd Cubex2contrasting
confidence: 99%
See 1 more Smart Citation
“…On the other hand, these finding are in contradiction with the results reached by another study (22) in which accelerated aging had an effect on color and translucency of different zirconia brands. The difference in results may be attributed to the different methodology of both studies.…”
Section: Dd Cubex2contrasting
confidence: 99%
“…The difference in results may be attributed to the different methodology of both studies. The later study (22) was conducted with different aging time (5 hours) and different thickness of the samples (0.5mm). It was previously explained that light reflectance increases when the thickness of the samples decreased as the thickness of the material has a major influence on translucency.…”
Section: Dd Cubex2mentioning
confidence: 99%
“…Our study showed that artificial aging for 10 h had no significant effect on the transparency of the tested zirconia materials (Figure 3). These results contradict with those of Walczak et al [12] where aging translucent zirconia with a thickness of 0.5 mm for 5 h significantly reduced the translucency. Untreated leucite reinforced glass-ceramic was more transparent than DD cubeX 2 and Prettau Anterior, thus porcelain veneering might be the best alternative when esthetics is of utmost importance.…”
Section: Transparencycontrasting
confidence: 99%
“…A few studies have investigated the optical properties of monolithic zirconia and especially its TP and CR but the results are very inhomogeneous due to variations in instrumentation, zirconia brand, the thickness of the specimens and parameters evaluated (Table S1 and Table 1) [45,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60,61,62,63,64,65,66,67,68,69]. For a comprehensive evaluation of the commercial products included in the following tables, their brand names and respective composition as reported by manufacturers or presented in associated references are presented in Table 1, at the end of the paper.…”
Section: Optical Propertiesmentioning
confidence: 99%